Characterization of Putative Iron Responsive Genes as Species-Specific Indicators of Iron Stress in Thalassiosiroid Diatoms - Whitney, LeAnn P.; Lins, Jeremy J.; Hughes, Margaret P.; Wells, Mark L.; Chappell, Phoebe D.; Jenkins, Bethany D. (Frontiers in Microbiology, 2011)
Iron (Fe) availability restricts diatom growth and primary production in large areas of the oceans. The physiological and molecular response to Fe limitation differs among diatom species, making it difficult to assess the Fe nutritional health of natural diatom populations. Accumulation of the photosynthetic proteins, ferredoxin (Fe-requiring) and flavodoxin (Fe-free), have been used to describe the Fe nutritional health of diatoms; however, these are bulk measurements and cannot be used to capture the complexity and variability in diatoms’ response to Fe stress. Species-specific molecular probes are better suited to discern the dynamics of Fe stress in natural assemblages. We examined the expression of genes involved in a putative copper-dependent Fe uptake system in Fe limited cultures of Thalassiosira pseudonana (CCMP 1335) to determine their use as sensitive gene-based biomarkers. Our results indicate that the expression of many putative Fe uptake genes in T. pseudonana are not linked to Fe status. We also compared ferredoxin and flavodoxin gene expression profiles in response to Fe stress in T. pseudonana and in Thalassiosira weissflogii (CCMP 1010), a closely related diatom isolated from the open ocean. In T. pseudonana, expression of flavodoxin and ferredoxin genes were not sensitive to Fe, but were sensitive to light and dark. These results were in stark contrast to gene expression patterns in T. weissflogii, where expression of flavodoxin was only detected in Fe limited cultures. Our findings highlight that Fe metabolism may differ among related diatoms and show a need to validate responses in different species as part of the development pipeline for genetic markers of Fe status in field populations.